Line Spread Test Results for Commercially Available the White Rice Porridge - Including the Effect of Four Types of Thickening Agents Added after Blending (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: commercial product; white rice porridge; lin spread test (LST); thickener